LEGAL CERTAINTY IN THE SUSPENSION OF CRIMINAL CASES DUE TO THE EXISTENCE OF CIVIL CASES IN THE LEGAL JURISDICTION OF THE KAMPAR RESORT POLICE - Hartono, Wandi; Harahap, Irawan; Pardede, Rudi (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
In the practice of criminal law enforcement in the jurisdiction of the Kampar Resort Police, legal issues often arise when a criminal case overlaps with a civil dispute. For instance, in cases involving alleged fraud or embezzlement, the reported party frequently argues that the matter is essentially a civil issue due to the existence of an agreement or contractual relationship between the parties. In this context, a legal question emerges regarding whether a criminal case may or should be suspended due to an ongoing or unresolved civil case. This situation creates tension between the principles of substantive justice, the doctrine of ultimum remedium in criminal law, and the principle of legal certainty. The objectives of this research are: to analyze legal certainty in the suspension of criminal cases due to the existence of civil cases within the jurisdiction of the Kampar Resort Police; to analyze the obstacles to legal certainty in such suspensions; and to analyze efforts to overcome these obstacles. The method used in this study is sociological legal research. Based on the findings, legal certainty in the suspension of criminal cases due to civil disputes in the Kampar Police jurisdiction has not been properly implemented. This is due to the legal provision that states criminal cases are not bound by civil proceedings. However, in practice, there is inconsistency in the application of this principle. In some instances, the criminal process continues despite ongoing civil litigation, while in others, it is suspended without a clear legal basis aside from the existence of a civil suit. The obstacles to legal certainty in the suspension of criminal cases include the lack of clear regulations and technical guidelines regarding the criteria and limits of suspension, limited protection for investigators' authority in making sensitive legal decisions, and conceptual confusion between criminal and civil matters, compounded by inadequate understanding among law enforcement officers. Efforts to overcome these obstacles include developing an internal policy framework in the form of technical guidelines or Standard Operating Procedures (SOPs) that detail when and under what conditions a criminal case may be suspended due to a civil dispute; the need for careful and well-documented legal assessments by investigators in every suspension process; and the establishment of official regulations or guidelines within the Indonesian National Police explicitly governing the limits and procedures for suspending criminal cases related to civil matters.